An experimental demonstration of a 4.5 kV 'Bi-mode Gate Commutated Thyristor' (BGCT) - Vemulapati, Umamaheswara; Arnold, Martin; Rahimo, Munaf; Vobecky, Jan; Stiasny, Thomas; Lophitis, Neophytos; Udrea, Florin (My University, 2015)
In this work we present the first experimental results of a Bi-mode Gate Commutated Thyristor (BGCT). The BGCT is a new type of Reverse Conducting-Integrated Gate Commutated Thyristor (RC-IGCT). In a conventional RC-IGCT, the IGCT and diode are integrated into a single wafer but they are fully separated from each other. The novel BGCT on the other hand features an interdigitated integration of diode- and GCT-areas. This interdigitated integration results in an improved diode as well as GCT area, better thermal distribution, soft turn-off/reverse recovery and lower leakage current compared to conventional RC-IGCTs. We have discussed the advantages of a new diode anode design in BGCT, which is shallower than that of the conventional RC-IGCT. We have successfully demonstrated the BGCT concept with 38 mm, 4.5 kV prototypes and compared the on-state, turn-off and blocking characteristics with conventional RC-IGCTs both in GCT- and diode-modes of operation.
Keywords: BGCT; Bi-mode GCT; High power semiconductor switch; IGCT; Reverse Conducting IGCT